Investigating motivation and language performance in ESL classrooms through the use of tablet applications / Parisa Nafissi Rad - Parisa Nafissi , Rad (2017)
Nowadays, technology plays an important role in the lives of our students and as a result, it has found its way into the modern classroom. According to different studies, using technology in the classroom has proven to be effective and can increase the engagement, motivation and performance of language learners. This study focused on the use of specific iPad applications for young Malaysian learners in an English language classroom. It was conducted using Dörnyei’s framework on motivation to determine if students’ engagement and motivation increased as a result of using iPad applications and whether that led to better performance. Additionally, the study discusses what preparations and considerations would be expected of teachers who plan to implement these applications in their classrooms. The study was conducted with two groups of students aged 13-15, over a period of 10 weeks in a private language school in Kuala Lumpur. Lessons were designed in two different ways, using iPad applications for the main group and the traditional methods for the comparison group. The performances between the two groups were compared using tests and observations. Qualitative questionnaire and interviews were used to examine whether learners of the main group enjoyed their lessons more than the comparison group due to the use of iPad applications. The results showed that learning with iPad applications enabled teachers to increase learners’ engagement and motivation through the ability to create interesting tasks and that led to better performance and participation of these learners.